HW4
HW4
HW4
1
State the following theorems:
(a) Cauchy’s Theorem
(b) Morera’s Theorem
(c) Cauchy integral formula.
(d) Cauchy integral formula for kth derivative.
Solution.
1
Math 562 Homework 4
2
Let f (z) = z 2 . Calculate the integral of f along the circle ∂D(2, 1) given by
R 2π
f (2 + eiθ )dθ is not zero. Yet ∂D(2,1) f (z)dz = 0. Give an explanation.
H
0
Solution.
Z 2π Z 2π
f (2 + eiθ )dθ = (2 + eiθ )2 dθ
0 0
Z 2π
= (4 + 4eiθ + ei2θ )dθ
0
= 8π.
H
On the other hand, by Cauchy theorem, ∂D(2,1) f (z)dz = 0.
2
Math 562 Homework 4
3
Let f be holomorphic in the annulus D(0, 2) \ D(0, 1). Show that for any
1 < r < R < 2, one has
I I
f (z)dz = f (z)dz.
∂D(0,r) ∂D(0,R)
3
Math 562 Homework 4
4
Compute each of the following line integrals:
H z2
(a) γ z−1 dz where γ describes the circle of radius 3 with center 0 and coun-
terclockwise orientation.
Solution. Define f (z) = z 2 . Since f is holomorphic and γ is the boundary
of a disk, by Cauchy Integral formula we have
z2
I I
f (z)
dz = dz
γ z−1 γ z−1
= 2πif (1)
= 2πi.
z
H
(b) dz where γ describes the circle of radius 1 with center 0
γ (z+4)(z−1+i)
and counterclockwise orientation.
Solution. The denominator of the integrand is zero at z = −4 and z =
1 − i. Both points are outside the unit circle. So we are integrating a
holomorphic function along a simple closed loop in a simply connected
domain. Hence I
z
dz = 0.
γ (z + 4)(z − 1 + i)
H z(z+3)
(c) dz where γ is the circle with center 2 + i with radius 3 with
γ (z+i)(z−8)
clockwise orientation.
Solution. Let γ 0 be the same as γ but with counterclockwise orientation.
I I
z(z + 3) z(z + 3)
dz = − dz
γ (z − 8)(z + i) γ 0 (z − 8)(z + i)
I I
1 z(z + 3) z(z + 3)
=− dz − dz
8+i γ0 z − 8 γ0 z+i
I
1 z(z + 3)
=− 0− dz
8+i γ0 z+i
2πi
=− − z(z + 3) z=−i
8+i
2πi(3 − i)
= .
8+i
The second equality above follows from Cauchy’s theorem since z(z+3)
z−8 is
holomorphic in the region bounded by γ. The third equality follows from
Cauchy integral formula.
4
Math 562 Homework 4
1
H
(d) ∂D(0,5) z(z−1)(z−2)(z−3)(z−4)
dz.
Solution. Since 0, 1, 2, 3, 4 ∈ D(0, 5), by Cauchy integral formula, we have
I
1
dz
∂D(0,5) z(z − 1)(z − 2)(z − 3)(z − 4)
I
1 1 1 1 1 1 1 1 1 1
= − + − + dz
∂D(0,5) 24 z 6 z − 1 4 z − 2 6 z − 3 24 z − 4
1 1 1 1 1
= 2πi − + − +
24 6 4 6 24
= 0.
1 z 2 +z
H
(e) . 2πi ∂D(1,5) (z−2i)(z+3)
dz.
Proof. Since 2i ∈ D(1, 5) and −3 ∈ D(1, 5), by Cauchy integral formula
we have
z2 + z
I
1
dz
2πi ∂D(1,5) (z − 2i)(z + 3)
1 z2 + z 1 z2 + z
I
1
= − dz
2πi ∂D(1,5) 2i + 3 z − 2i 3 + 2i z + 3
1 1
(2i)2 + (2i) − (−3)2 + (−3)
=
2i + 3 3 + 2i
−34 − 14i
= .
5 + 12i